PEMBIASAN REVOLUSI PENGETAHUAN: PEMIKIRAN KUHN DAN REFLEKSI SEJARAH KEHIDUPAN PROF. DUDUNG DARUSMAN - Handoyo Handoyo (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2018)
Most of the literature related to the development of forestry science in Indonesia explains that there has been a shift in the forest management paradigm from timber-based forest supremacy management paradigm to community-based forest management paradigm. This paper aims to argue that it is biased scientifically. This paper is presented based on research by using narrative approach and analysis of Dudung Darusman life history, that shows that the process of shifting attention to civil/communal supremacy over common property, and seeking justification for the community-based forest management perspective as a paradigm, can not be called as knowledge revolution that which lead to paradigm shift. The orchestration of particular political and power practices as well as their manifestations in the more paradigmatically external national forest management are responsible for the refraction.